2021
DOI: 10.1111/nyas.14715
|View full text |Cite
|
Sign up to set email alerts
|

Math anxiety differentially impairs symbolic, but not nonsymbolic, fraction skills across development

Abstract: Although important for the acquisition of later math skills, fractions are notoriously difficult. Previous studies have shown that higher math anxiety (MA) is associated with lower performance in symbolic fraction tasks in adults and have suggested that MA may negatively impact the acquisition of fractions in children. However, the effects of MA on fraction skills in school‐aged children remain underexplored. We, therefore, investigated the impact of MA on the performance of younger (second and third graders) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…was not affected by math anxiety. 26 In fact, the nonsymbolic ratio task in their study was close to situational mathematics, which is an intuitive representation of fractions, and thus is less associated with math anxiety.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…was not affected by math anxiety. 26 In fact, the nonsymbolic ratio task in their study was close to situational mathematics, which is an intuitive representation of fractions, and thus is less associated with math anxiety.…”
Section: Discussionmentioning
confidence: 91%
“…However, symbolic mathematics is the most abstract and generalized; thus, it is not easy for beginners to understand, and it can easily induce math anxiety. A recent study found that higher math anxiety was associated with lower performance in symbolic fraction tasks (e.g., identify the larger fraction, 7/9 vs. 1/4), but nonsymbolic ratio processing (e.g., identify the larger ratio of two pairs of lines) was not affected by math anxiety 26 . In fact, the nonsymbolic ratio task in their study was close to situational mathematics, which is an intuitive representation of fractions, and thus is less associated with math anxiety.…”
Section: Discussionmentioning
confidence: 97%
“…Studies providing converging evidence from psychometric, neurophysiological, and cognitive data remain scarce. [37][38][39][40][41][42][43] Despite their relative difficulty, in comparison to questionnaires, such studies might bring new insights into the understanding of MA; they might prove particularly useful because they allow the tracing of neurophysiological/cognitive responses while performing anxiety-inducing mathematics tasks. Nevertheless, the evidence so far shows that questionnaires remain a more reliable measure of MA than implicit MA measures.…”
Section: Construct Validitymentioning
confidence: 99%
“…Going beyond self‐description, studies using other measures (e.g., neurophysiological and cognitive) in the context of MA are relatively scarce and focus on group‐level differences. Studies providing converging evidence from psychometric, neurophysiological, and cognitive data remain scarce 37–43 . Despite their relative difficulty, in comparison to questionnaires, such studies might bring new insights into the understanding of MA; they might prove particularly useful because they allow the tracing of neurophysiological/cognitive responses while performing anxiety‐inducing mathematics tasks.…”
Section: Blank Spots and The Future Research Agendamentioning
confidence: 99%
“…Furthermore, the relation between mathematics anxiety responses and performance on the guided multiplicative relations task was very low. Performance on tasks including non-symbolic quantities may be less correlated with mathematics anxiety, because they are less tied to formal mathematics instruction at this age (Starling-Alves et al, 2022). Nevertheless, these findings suggest that mathematics anxiety may not substantially hinder students' tendency to recognize mathematical relations and apply their mathematical knowledge in everyday-like situations.…”
Section: Discussionmentioning
confidence: 78%